2023
DOI: 10.20944/preprints202306.0202.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Serum C-Reactive Protein to Albumin Ratio as a Reliable Marker of Diabetic Neuropathy in Type 2 Diabetes Mellitus

Abstract: Type 2 diabetes mellitus may be complicated with chronic complications including diabetic neuropathy (DN). Timely diagnosis is crucial in treatment and maybe reversal of this complication. C reactive protein to albumin ratio (CAR) is considered as a marker of inflammation in various diseases that characterized with acute or chronic inflammation. Since diabetic neuropathy and type 2 diabetes mellitus are also associated with chronic, low grade inflammation, we aimed to study CAR levels of type 2 diabetic subjec… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…Moreover, increased C-reactive protein levels were noted in subjects with diabetic neuropathy when compared to those without diabetic neuropathy [ 26 ]. Subsequently, a recent study confirmed the previous works by reporting increased C-reactive protein levels in diabetic neuropathy subjects compared to those of the diabetic patients without neuropathy [ 27 ]. Another inflammatory marker, high sensitivity C-reactive protein levels, were higher in the diabetic patients with diabetic foot ulcers, a complication closely associated with diabetic neuropathy, than those in diabetic patients without foot ulcers [ 28 ].…”
Section: Discussionsupporting
confidence: 77%
“…Moreover, increased C-reactive protein levels were noted in subjects with diabetic neuropathy when compared to those without diabetic neuropathy [ 26 ]. Subsequently, a recent study confirmed the previous works by reporting increased C-reactive protein levels in diabetic neuropathy subjects compared to those of the diabetic patients without neuropathy [ 27 ]. Another inflammatory marker, high sensitivity C-reactive protein levels, were higher in the diabetic patients with diabetic foot ulcers, a complication closely associated with diabetic neuropathy, than those in diabetic patients without foot ulcers [ 28 ].…”
Section: Discussionsupporting
confidence: 77%
“…Early detection and intervention can prevent blindness caused by DR [4,5], however delayed treatment may result in severe and irreversible consequences. Emerging evidence suggests that chronic inflammation may play a role in DR progression and possibly make the untreated PDR worse in patients failed to be identified in time [10][11][12][13][14]. While established methods for detecting DM [1] and DR [2,3] exist, this research sheds light on the complex and diverse factors contributing to delayed presentation of DR in Chinese patients, an area previously unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging research [10,11], highlights a complex relationship between inflammation and various diabetic complications, including diabetic neuropathy [12], DR [13], and diabetic nephropathy [14]. This growing body of evidence suggests that the inflammatory characteristics of Type 2 DM may contribute to the progression of DR [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Similarly, low-grade inflammation is important in the development of chronic diabetic complications, such as diabetic nephropathy, 7 retinopathy, 8 and neuropathy. 9 Several studies have confirmed that the onset and development of many cardiovascular diseases are closely related to inflammation. 10 For example, patients with coronary heart disease are in a state of increased inflammatory load.…”
Section: Introductionmentioning
confidence: 99%